2020
DOI: 10.1038/s41598-020-63212-3
|View full text |Cite
|
Sign up to set email alerts
|

Infant Corpus Callosum Size After Surgery and Critical Care for Long-Gap Esophageal Atresia: Qualitative and Quantitative MRI

Abstract: previous studies in preterm infants report white matter abnormalities of the corpus callosum (cc) as an important predictor of neurodevelopmental outcomes. our cross-sectional study aimed to describe qualitative and quantitative cc size in critically ill infants following surgical and critical care for longgap esophageal atresia (LGeA)-in comparison to healthy infants-using MRi. non-sedated brain MRi was acquired for full-term (n = 13) and premature (n = 13) patients following treatment for LGEA, and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 62 publications
3
32
0
Order By: Relevance
“…In the case of the patient, imaging analysis is based on the changes in brain structures related to skull volume. Recently, Mongerson et al reported changes in the CC employing a method similar to the one we used here to evaluate degenerative processes in the brain (27). They normalized the quantitative differences in the CC (in %) using total brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the patient, imaging analysis is based on the changes in brain structures related to skull volume. Recently, Mongerson et al reported changes in the CC employing a method similar to the one we used here to evaluate degenerative processes in the brain (27). They normalized the quantitative differences in the CC (in %) using total brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot MRI study builds on our previous reports 13 , 17 , 19 using data from the same infant study cohort. Our study received ethical approval from Boston Children’s Hospital Institutional Review Board as a “no more than minimal risk” study and recruitment was possible thanks to The Esophageal and Airway Treatment Center at Boston Children’s Hospital ‐ a premier program designed to treat infants born with thoracic noncardiac and gastrointestinal congenital anomalies, especially LGEA.…”
Section: Methodsmentioning
confidence: 94%
“…A representative timeline illustrating the sequence of perioperative critical care for Foker process 20 was previously presented, 18,23 while associations between individual MRI end‐point measures (e.g., number of cranial MRI findings and brain volumes) and the clinical measures of care as to assess the severity of underlying disease in cohort subjects will be presented elsewhere. Methodological approach for recruitment criteria and MRI scanning were previously described 13,17,19 . Briefly, informed written parental consent was obtained for non‐sedated research brain MRI participation, in accordance with the Declaration of Helsinki and Good Clinical Practice guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations